Preparation and Characterization of Porous Carbon Material from Banana Pseudo-Stem (Dhaka University Journal of Science, 2024)
In this work, pseudo-stem of a banana plant was used as a sustainable and affordable source to prepare porous carbon materials (PCM) on a large scale. After fine treatment, the material was annealed at 500, 600, and 700 °C using a tube furnace under nitrogen flow. The prepared materials were characterized by Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). FT-IR spectra show that the broad peak at the range of 1110-1160 cm-1 comes from the superimposed peaks of C-N for a single or more than one functional group which debunks the possibility of generating nitrogen-doped carbon. TEM and SEM analyses confirmed the porous structure of PCM with the pores connected to one, and a spongy structure was observed in the prepared carbon material. XRD analysis revealed that the carbon materials are crystalline. XPS investigation provided information regarding the dimension of which elements are present in the valence states and constituent elements, depicting the presence of a dominant graphitic C1speak at approximately 284 eV, along with a distinct O1s peak at around 532 eV. Additionally, a relatively weaker N1s peak (approximately 400 eV) was observed.Dhaka Univ. J. Sci. 72(1): 63-70, 2024 (January)